Making Climate Services Work for Africa's Farmers at Scale - Hansen, James; Bradley-Cook, Julia; Apotsos, Alex; Blumenstock, Ali; Carr, Edward R.; Vaughan, Catherine (Climate Links, 2020)
The substantial body of knowledge about good practice in climate services suggests that making climate services work for farmers at a national scale requires managing tradeoffs between meeting farmers’ context-specific needs and providing cost-effective services at scale.